Blindness to risk: why institutional investors ignore the risk of stranded assets*. (2nd January 2017) - Silver, Nicholas
ABSTRACT: There has been an apparent resistance amongst mainstream investors to integrate the risk of stranded assets into investment decisions. This paper considers if the structure of the investment chain causes investors to be blind to risks such as stranded assets. This paper considers how the interaction between financial economic theory, regulation and the practices of the fund management industry gives rise to the way the industry analyses and manages risk. The paper draws on a mixture of academic literature and the author's own experience of industry practice. The paper finds that institutional investors are constrained to measure risk in relation to a benchmark; risk becomes a function of volatility and divergence from peers. The risk of stranded assets is invisible in the decision-making chain. The industry is further constrained by its culture, regulation and inappropriate incentives. The paper concludes that integrating stranded asset risk requires a drastic overhaul of the regulation of, and theory used in, the investment chain. This would better align the investment industry with the long-term capital allocation requirements of society.